A new multiplexer, demultiplexer and data recovery rules for duty cycle division multiplexing technique for optical communication. - Abas @ Ismail, Ahmad Fauzi (2009)

(untitled)
A new multiplexer design, demultiplexer design, and set of data recovery rules are presented here. In the proposed multiplexer architecture, the multiplexing process performs in electrical domain using a simple electrical adder for multiplexing any number of users. This architecture required only one optical modulator to modulate the multiplexed signals with the optical carrier. The proposed demultiplexer required one sampling circuit less than the Cv-DCDM. By proposing the new set of the data recovery rules, performance of the CV-DCDM is improved significantly in terms of CD tolerance, OSNR, and SPM effect. Also, the proposed data recovery rules support the automatic error corrections. Using the DCDM, channel utilization of WDM system can be increased tremendously based on the number of available RZ duty cycle.